Recepção de oócitos: estudo retrospectivo para análise da técnica - Vicensoto, Wagner (2004)
The oocyte donation and reception program is a technique in which female gametes from a woman (donor) are donated to other woman (recipient) in order to be fertilized with the respective recipient s husband spermatozoa. The present study analyzed fourteen patients who underwent 21 cycles of egg reception by this assisted reproductive medical technique at the Reproductive Medicine Institute (RMI) of São José do Rio Preto-SP, in the period from January 1998 to December 2002. The recipients age ranged between 29 to 49 years; the mean age 40 years. Ten patients (71.5%) did not report previous gestation, therefore considered women with primary infertility. In order to perform the indications to the oocyte reception we classified five patients (35.7%) as having premature menopause, five (35.7%) as ovarian failure, three (21.5%) as physiological menopause, and one (7.1%) as unsuccessful responder to previous treatments. Only six patients (42.9%) had not undergone previous infertility treatments. In 92.9% of the patients, the assisted reproductive technique used was the Intracytoplasmic Sperm Injection (ICSI). The number of embryos transferred per cycle was between two and four. A total of 21 cycles were performed with a rate of 52.4% of gestation per cycle and 71.5% gestation per patient. The rate of multiple gestations was 27.3%. Regarding the gestation evolutions, it was observed a rate of 36.4% of miscarriage and 63.6% of ongoing pregnancies, in which 9.1% had premature delivery, and 54.5% had full term delivery without intercurrences. The rate of home baby was 50%. The oocyte donation and reception program showed to be a successful technique, with excellent results, providing a feasible and ethic way of getting pregnant some selected patients who have otherwise been considered as having an infertility reserved diagnostic.